Nutrient recovery technologies for management of blackwater: A review - Wang, Xuemei; Chen, Jinxin; Li, Zifu; Cheng, Shikun; Mang, Heinz-Peter; Zheng, Lei; Jan, Inayatullah; Harada, Hidenori (Frontiers in Environmental Science, 2023)
Nutrient recovery and recycling are of great importance in sustainable development. Blackwater (BW) refers to wastewater from toilets, which contains feces, urine, water, and toilet paper from flush toilets. The highly concentrated nutrients of blackwater could be collected through source separation and treated adequately to recover nutrients efficiently and economically. The review intends to give an overview of the characteristics of BW and different techniques to recover nutrients and other valuable products. A number of these technologies are currently under development or being tested at laboratory or pilot scale. The perspective for blackwater nutrient recovery technologies is very positive due to their great potential. For application of source-oriented sanitation infrastructure and systems, there is still a long way to go for development of commercial technologies and valuable products.